Nanocatalysis: Academic Discipline and Industrial Realities - Sandro Olveira; Simon P. Forster; Stefan Seeger (Journal of Nanotechnology)
Nanotechnology plays a central role in both academic research and industrial applications. Nanoenabled products are not only found in consumer markets, but also importantly in business to business markets (B2B). One of the oldest application areas of nanotechnology is nanocatalysis—an excellent example for such a B2B market. Several existing reviews illustrate the scientific developments in the field of nanocatalysis. The goal of the present review is to provide an up-to-date picture of academic research and to extend this picture by an industrial and economic perspective. We therefore conducted an extensive search on several scientific databases and we further analyzed more than 1,500 nanocatalysis-related patents and numerous market studies. We found that scientists today are able to prepare nanocatalysts with superior characteristics regarding activity, selectivity, durability, and recoverability, which will contribute to solve current environmental, social, and industrial problems. In industry, the potential of nanocatalysis is recognized, clearly reflected by the increasing number of nanocatalysis-related patents and products on the market. The current nanocatalysis research in academic and industrial laboratories will therefore enable a wealth of future applications in the industry.